Enhancing the HVRT and LVRT Capabilities of DFIG-based Wind Turbine in an Islanded Microgrid - Safaei, A.; Hosseinian, S. H.; Askarian Abyaneh, H. (Engineering, Technology & Applied Science Research, 2017)
Doubly fed induction generator (DFIG) based wind turbines are very sensitive to grid voltage variations. Therefore, low-voltage-ride-through (LVRT) and high-voltage-ride-through (HVRT) capabilities are employed to improve DFIG performance during grid faults and voltage swell events. In this paper, a superconducting magnetic energy storage (SMES) device with a PWM voltage source converter and a DC-DC chopper is proposed to enhance the DFIG LVRT and HVRT capabilities in an islanded microgrid simultaneously. The simulation results demonstrate that the SMES absorbs or releases energy from/to the microgrid during voltage swell events and fault condition respectively and consequently, improves the DFIG performance and enhances the DFIG LVRT and HVRT capabilities. The effectiveness of the proposed method is validated through detailed simulations in PSCAD/EMTDC.